Effects of Early Mobilization Protocol on Cognitive Outcome after Cardiac Surgery - Ziyaeifard, Mohsen; Gholami Beh Khoo, Fatemeh; Lotfian, Sara; Azarfarin, Rasoul; Aminnejad, Reza; Alikhani, Rosa; Yousefi Moghadam, Manizheh (Annals of Anesthesiology and Critical Care, 2018)
Background: This study aimed at determining the effects of implementation of “early mobilization protocol” on incidence of cognitive dysfunction after cardiac surgery. Methods: In a randomized controlled trial, 80 adult patients, who had undergone elective cardiac surgery were randomly assigned to intervention (early mobilization protocol; n = 40) and control (routine physical therapy; n = 40) groups. Early mobilization was initiated from the first post-op morning and continued until discharge from the ICU. Cognitive dysfunction was assessed by the mini mental state examination (MMSE) questionnaire. The MMSE questionnaire was completed at three occasions for every patient: one day before surgery, second post-op day, and at the time of discharge from the intensive care unit (ICU). Results: Preoperative cognitive status had no difference between the two groups (P = 0.310). Post-op cognitive dysfunction was significantly more commonly reported in the control group. The MMSE scores were higher in early mobilized patients compared to the control group on the first post-op day (median: 28; inter quartile range: 26 to 30 versus median: 25; IQR: 22 to 27; p = 0.001) and at the time of discharge from the ICU (median: 29; IQR: 28 to 30 versus median: 26; IQR: 25 to 28; p = 0.001). In multivariate analysis, duration of tracheal intubation and “early mobilization protocol” had significant effects on patients’ length of ICU stay. Conclusions: Implementation of early mobilization protocol has positive effects on cognitive outcome and ICU stay after cardiac surgery.